COUNTER-HEGEMONY PRACTICE A LA GOJEK DRIVER-PARTNERS’ SELEBGRAMS - Irsanti Widuri Asih; Heru Nugroho; Budiawan Budiawan (International Conference on Social and Islamic Studies, 2021)
The sharing economy business model implemented by Gojek posits its motorbike drivers as partners with the status of independent contractors. However, some empirical studies show the practice of an asymmetrical working relationship and places Gojek's driver-partners as the exploited party. Gojek's business is hegemonic since the exploited practices are wrapped in affective ways, e.g. through the concept of partnerships that glorify freedom and flexibility and the gamification strategy used in the application. In the context of this new emerged business practice, there is a vagueness about the legal status of the driver-partners. This is merely a corporate strategy to avoid the obligation to provide social protections for drivers because of their non-employee status. However, in the midst of hyper-exploitation practices carried out by the corporation, several studies have revealed actions of resistance conducted by driver-partners, ranging from demonstrations, boycotts, to various uses of application modification. In contrast to previous studies, this paper particularly elaborates a form of counter-hegemony action carried out by three Gojek driver-partners who become selebgram (stands for the celebrities of Instagram in Bahasa Indonesia). Their affliction as Gojek driver-partners who often experience income deficiency due to high competitiveness and complicated platform work systems, are used to accumulate social capital and economic capital.